Implementasi Metode Naïve Bayes untuk Pemilihan Pengobatan Tumor Tulang - Siti Ernawati; Aisyah Putri Faisal (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2022)
Decision support system is an interactive system that helps decision making through the use of data and decision models to solve problems that are semi-structured and unstructured. This study implements the Naive Bayes method because this method has advantages compared to other methods, and the Naive Bayes method is a decision-making to predict probability-based using the values entered, in the form of criteria needed. Bone Tumor is a primary malignancy in children and adolescents, which attacks in adolescents aged 10 to 20 years. Treatment of osteosarcoma can be done by radical amputation or limb salvage procedure, depending on the severity of the tumor. The purpose of this study was to obtain treatment information selected by bone tumor patients using medical record data with sample collection method. In the hope that this information can be a consideration for bone tumor patients who are still hesitant to complete treatment in order to be eager to complete treatment. The results obtained the number of cases of bone tumors is as many as 19 cases, and Limb Salvage is the most widely chosen treatment by bone tumor patients. This study also used rapidminer to see the results of validation. The classification results obtained are accuracy value 80%.